A myocardial infarction detected in an unusual way - Massimo Barakat; Enrico Bertagnin; Lorenzo Mulazzani; Francesco Galuppi; Sanda Giovanna Nizzardo (Emergency Care Journal)
An 86-year-old man presented to the emergency department with abdominal pain in the left iliac fossa and constipation in the previous three days. Laboratory tests revealed an increase in C-reactive protein levels (22.37 mg/dL), white blood cell count (12.38x109/L), neutrophil count (10.07x109/L), and hyperglycemia (237 mg/dL). An abdominal contrast-enhanced computed tomography scan ruled out acute abdominal pathological findings but showed a marked hypoperfusion of the mid-apical anterior wall and the apex of the left ventricle. A subsequent electrocardiogram revealed an excessive ST elevation (>5 mm) and a negative QRS complex in precordial leads (from V1 to V6). Serial assays of high-sensitivity troponin I showed a plateau phase (from 15696.4 to 15479.3 ng/L). Echocardiography revealed a left ventricle dilated and severely hypokinetic (ejection fraction of approximately 15-20%). A diagnosis of subacute myocardial infarction with severe dysfunction of the left ventricle was therefore made.